VDC_100102370126.0X000001. Issue 3 (March 2018) - Beal, Eliza W.; Saunders, Neil D.; Kearney, Joseph F.; Lyon, Ezra; Wei, Lai; Squires, Malcom H.; Jin, Linda X.; Worhunsky, David J.; Votanopoulos, Konstantinos I.; Ejaz, Aslam; Poultsides, George; Fields, Ryan C.; et al.
The objective of this study is to assess the accuracy of the American College of Surgeons National Surgical Quality Improvement Program online risk calculator for estimating risk after operation for gastric cancer using the United States Gastric Cancer Collaborative. Nine hundred and sixty-five patients who underwent resection of gastric adenocarcinoma between January 2000 and December 2012 at seven academic medical centers were included. Actual complication rates and outcomes for patients were compared. Most of the patients underwent total gastrectomy with Roux-en-Y reconstruction (404, 41.9%) and partial gastrectomy with gastrojejunostomy (239, 24.8%) or Roux-en-Y reconstruction (284, 29.4%). The C-statistic was highest for venous throm-boembolism (0.690) and lowest for renal failure at (0.540). All C-statistics were less than 0.7. Brier scores ranged from 0.010 for venous thromboembolism to 0.238 for any complication. General estimates of risk for the cohort were variable in terms of accuracy. Improving the ability of surgeons to estimate preoperative risk for patients is critically important so that efforts at risk reduction can be personalized to each patient. The American College of Surgeons National Surgical Quality Improvement Program risk calculator is a rapid and easy-to-use tool and validation of the calculator is important as its use becomes more common.